Recovering the Lost Soul: Older Women's Reflections on Past Intrafamilial Child Sexual Abuse. (April 2023) - Winterstein, Tova Band; Avieli, Hila; Gichaz, Mili
Intrafamilial child sexual abuse (IFCSA) is a social problem with longstanding effects on victims' lives. While scholarly literature has focused on the adverse aftermath of sexual abuse, only a few studies have acknowledged older women's perspectives on their experience of IFCSA and their journey of healing and recovery. The aim of the present study was to explore how older survivors of IFCSA construct and shape their experience of healing in later life and the meaning they assign to this process. Narrative inquiry was selected to explore the narratives of 11 older women survivors of IFCSA. Participants were interviewed using a biographical narrative interviewing method. The narratives were then transcribed and analyzed using thematic, structural, and performance analyses. Four major themes emerged from the participants' narratives: Achieving closure; Spiritual framing of IFCSA as a platform for self-growth; Becoming whole in old age; and Looking to the future after IFCSA. During the aging years, IFCSA survivors may redefine their identity and their place in the world. Using life review processes, older women in this study were striving to heal and reconcile with their past.